STUDY OF PREFERENCE LEVEL OF IWAK SAMBAL (SALAWAK) BASED ON BY-PRODUCTS OF CATFISH FILLET (PANGASIUS SP) - Panjaitan, Pola S. T.; Panjaitan, Tina F.C.; Rina, Dede; Soeprijadi, Liliek; Mukhaimin, Iman (Jurnal Perikanan Unram, 2024)
Milkfish is a popular brackish water fishery commodity with increasing demand. Feed is one of the factors determining the success its cultivation because affects growth and production costs. The price of feed continues to increase, so it is expected that the use of alternative feeds with lower prices but still of high quality. Pterygoplichthys pardalis meal can be a substitute for commercial fishmeal. The purpose of this study was to analyze the growth response of milkfish using P. pardalis meal (TS) as the main protein source in addition to commercial fishmeal (TK). Milkfish measuring ±7.0 cm and weighing ±4.35 g were reared for 60 days. The percentage of TS as treatment, treatment A 25%, B 30%, C 35% and D commercial feed. Other feed ingredients used were commercial fishmeal, cornmeal, fine bran, copra meal, vitamins and minerals. The feed dose was 5%/body weight and the frequency of feeding was 3 times a day. Parameters observed were weight and length growth, survival and feed conversion and water quality. Using a completely randomized design with 4 treatments and 3 replicates. Data were analyzed using ANOVA and Duncan’s further test, water quality was analyzed descriptively. Treatments affect growth and feed conversion but have no effect on survival rate, water quality is well tolerated. There was a tendency that the more TS was used, the higher the feed protein content and the better the growth and feed conversion responses. The use of 35% TS is better and the response is the same as treatment D. TS can be alternative protein source to replace TK in milkfish feed.